SIMPLE CONVERSATION SYSTEM ON SOCIAL ROBOTS WITH LEVENSHTEIN ALGORITHM - Haris Yuana (JOSAR (Journal of Students Academic Research), 2018)
Robots in the industrial era 4.0 are not only required to be able to help or replace human work. Humans have positioned robots not only as machines, but also as friends. Like a friend, the robot must be able to interact, communicate, and respond. This phenomenon raises the term social robot, which is a robot that can interact socially like humans do with each other. Robot interaction with humans can be verbal communication (conversation), text, social-media, physical movement, or artificial intelligence (AI). This paper focuses on discussing social robot interactions in (verbal) conversations. Robot conversation patterns can be built simply by applying the Levenshtein algorithm to the database search method to get conversation responses. With this method the robot can provide a response that relates to the topic that the opponent is talking about without going too far.